2014
DOI: 10.1055/s-0034-1383357
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Twelve Metabolites of Isocorynoxeine in Rat Urine and their Neuroprotective Activities in HT22 Cell Assay

Abstract: Isocorynoxeine, one of the major alkaloids from Uncaria Hook, shows the effects of lowering blood pressure, vasodilatation, and protection against ischemia-induced neuronal damage. In this paper, the metabolism of isocorynoxeine was investigated in rats. Twelve metabolites and the parent drug were isolated by using solvent extraction and repeated chromatographic methods, and determined by spectroscopic methods including UV, MS, NMR, and CD experiments. Seven new compounds were identified as 11-hydroxyisocoryno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Comparing the retention time, accurate mass and diagnostic fragment ions with those of our previous studies (Yuan et al, ; Zhao et al, ), M13, M16, M18 and M23 were tentatively identified as isocorynoxeinic acid, 18,19‐dehydrocorynoxinic acid, corynoxeinic acid and 18,19‐dehydrocorynoxinic acid B, respectively, which were hydrolyzed metabolites of ICO (P15) or COR (P17). When identifying the tetracyclic oxindole alkaloids possessing a 7S configuration, there were two diagnostic fragmentation ions, m/z 201 (C 12 H 13 N 2 O) and 187 (C 11 H 11 N 2 O), which were reported in our previous studies (Qi, Chen, Sun, Simpkins, & Yuan, ; Zhao et al, ). Therefore, the 7S configuration of M13 and M16 was confirmed.…”
Section: Resultsmentioning
confidence: 58%
“…Comparing the retention time, accurate mass and diagnostic fragment ions with those of our previous studies (Yuan et al, ; Zhao et al, ), M13, M16, M18 and M23 were tentatively identified as isocorynoxeinic acid, 18,19‐dehydrocorynoxinic acid, corynoxeinic acid and 18,19‐dehydrocorynoxinic acid B, respectively, which were hydrolyzed metabolites of ICO (P15) or COR (P17). When identifying the tetracyclic oxindole alkaloids possessing a 7S configuration, there were two diagnostic fragmentation ions, m/z 201 (C 12 H 13 N 2 O) and 187 (C 11 H 11 N 2 O), which were reported in our previous studies (Qi, Chen, Sun, Simpkins, & Yuan, ; Zhao et al, ). Therefore, the 7S configuration of M13 and M16 was confirmed.…”
Section: Resultsmentioning
confidence: 58%
“…It was thought that these alkaloids can metabolize to their 10-and 11-hydroxyl metabolites, such as rhynchophylline (32), isorhynchophylline (40), corynoxeine (34) and isocorynoxeine (78) (Wang et al, 2010a;2010b;Qi et al, 2015). The specific inhibition of CYP isozymes can regulate their hydroxylation metabolites at C-10 and C-11 (Wang et al, 2010a(Wang et al, , 2010b.…”
Section: Pharmacokinetic and Metabolismmentioning
confidence: 99%
“…Different from above compounds, hirsutine (1) and hirsuteine (2) only produced their 11-hydroxy metabolites in rats (Nakazawa et al, 2006). Recently, Chen et al 2014 andQi et al, 2015 reported that the possible oxidation and hydroxylation metabolites of isorhynchophylline (40) and isocorynoxeine (78), which was important to further understand their metabolites Qi et al, 2015). Kushida et al (2013) further investigated the pharmacokinetics of Uncaria hook alkaloids after oral administration of Yokukansan (0.25, 1 and 4 g/kg).…”
Section: Pharmacokinetic and Metabolismmentioning
confidence: 99%
“…The biliary metabolites of IC or C, 10-or 11-hydroxy-IC or C and their 10-or 11-O-glucuronides were identified [17,18]. In our recent study, 12 urinary metabolites of IC were identified, mainly including 5-ox- [18,19]-5-oxoisocorynoxeine (oxi- [18,19]-5-O-IC) [19]. These studies suggest that both phase I and phase II metabolisms may play important roles in oxindole metabolism in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, a diagnostic fragment ion that was 16 Da different from that of IC at m/z 201.1030 (C 12 H 13 N 2 O) was detected at m/z 217.09 (C 12 H 13 N 2 O 2), suggesting that M 1 and M 3 possessed a 7S configuration according to the diagnostic fragment ion of IC, C, DAC and DCAB. Since IC undergoes demethylation at C-17, hydroxylation at C-10 or 11, and/or reduction of the 16-double bond in the in vivo metabolism[19],…”
mentioning
confidence: 99%